Decision making in management of proximal fifth metatarsal fracture: a short review - Haslan H,; Zar, Chi T; Mohd Yusoff Yahaya, (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2016)
Fifth metatarsal bone fracture is one of the most commonest fractures of the foot. The decision for surgical or conservative approach is still inconclusive. Scoring system, decision analysis model and classification system are established to weigh between surgical and conservation approaches. Its unique anatomy and surgical complication influence decision on optimal surgical approach. Therefore, the present review attempts to look at factors that might influence decision making in management of fifth metatarsal fracture.